Hippocampal aspiration lesions fail to impair performance of a delayed alternation GO/NO-GO task. - Foster, J; Rawlins, J (1992)
Rats with hippocampal aspiration lesions (HIPP), cortical control lesions (CORT) or sham operations (SHAM) were trained on a delayed alternation GO/NO-GO task, in which responding was reinforced on odd-numbered GO trials but was not reinforced on even-numbered NO-GO trials. The number of responses required to obtain reinforcement, and the length of the inter-trial intervals (ITIs), were varied in different stages of the experiment. These systematic parametric manipulations were conducted in order to compare the roles of intra- and inter-trial information and the temporal spans which could be bridged in performing the task across the three different lesion groups. In addition, at a later stage of testing interference was introduced during the ITI to investigate its effect on task performance. The differences observed between the HIPP, CORT and SHAM groups were generally non-specific for trial type, with HIPP animals responding more overall on both NO-GO and, to a lesser extent, GO trials following each of the ITIs used. The results were consistent with the behavioural inhibition theory of hippocampal function, but not with the temporal discontiguity or working memory models. These surprising findings contrast sharply with those observed following an electrolytic lesion of the hippocampus, which has been reported to produce a delay-dependent impairment of performance on the GO/NO-GO task in rats using a very similar procedure. It is speculated that differences in performance following aspiration and electrolytic lesions may be at least partially attributable to rats adopting different response strategies induced by ITI differences in the two tasks. However, the results also raise an important question concerning the assumed equivalence of aspiration and electrolytic lesions of the hippocampus. The possibility that an interaction between procedural and lesion differences may contribute to the discrepant findings is also considered. The findings illustrate the sensitivity of the hippocampal mnemonic effect on what has become an established testing procedure in the hippocampal literature.